Testing Augmented Reality for Eliciting Cue-Provoked Urges to Smoke: Toward Moving Cue-Exposure Into the Real World. Issue 5 (4th December 2020) - Brandon, Karen O; Vinci, Christine; Kleinjan, Marloes; Hernandez, Laura M; Sawyer, Leslie E; Sutton, Steven K; Brandon, Thomas H
Abstract: Background: Cue exposure for extinguishing conditioned urges to smoking cues has been promising in the laboratory, but difficult to implement in natural environments. The recent availability of augmented reality (AR) via smartphone provides an opportunity to overcome this limitation. Testing the ability of AR to elicit cue-provoked urges to smoke (ie, cue reactivity [CR]) is the first step to systemically testing the efficacy of AR for cue exposure therapy. Objectives: To test CR to smoking-related AR cues compared to neutral AR cues, and compared to in vivo cues. Methods: A 2 × 2 within-subject design comparing cue content (smoking vs. neutral) and presentation modality (AR vs. in vivo) on urge response. Seventeen smokers viewed six smoking-related and six neutral cues via AR smartphone app and also six smoking and six neutral in vivo cues. Participants rated their urge to smoke and reality/co-existence of the cue. Results: Average urge to smoke was higher following smoking-related AR images (Median = 7.50) than neutral images (Median = 3.33) ( Z = −3.44; p = .001; d = 1.37). Similarly, average urge ratings for in vivo smoking-related cues (Median = 8.12) were higher than for neutral cues (Median = 2.12) (Z = −3.44; p = .001; d = 1.64). Also, greater CR was observed for in vivo cues than for AR cues ( Z = −2.67, p = .008; d = .36). AR cues were generally perceived as being realistic and well-integrated. Conclusions: CR was demonstrated with very large effect sizes in response to AR smoking cues, although slightly smaller than with in vivo smoking cues. This satisfies the first criterion for the potential use of AR for exposure therapy. Implications: This study introduces AR as a novel modality for presenting smoking-related stimuli to provoke cue reactivity, and ultimately to conduct extinction-based therapy. AR cues presented via a smartphone have the advantage over other modes of cue presentation (pictures, virtual reality, in vivo, etc.) of being easily transportable, affordable, and realistic, and they can be inserted in a smokers' natural environment rather than being limited to laboratory and clinic settings. These AR features may overcome the generalizability barriers of other methods, thus increasing clinical utility for cue exposure therapies.